Assessing the potential distribution of Myracrodruon urundeuva Allemão (Aroeira) in the Caatinga under climate change scenarios - da Costa, Douglas Batista; de Lima, Robson Borges; Caraciolo Ferreira, Rinaldo L.; de Paula, Alessandro; de Oliveira, Cinthia Pereira; Aleixo da Silva, José A.; Gomes, Joselane P.; Santana, Mariana M. M.; Pereira, Ana Luisa L. (Frontiers in Forests and Global Change, 2025)
The Caatinga, a seasonally dry tropical forest in northeastern Brazil, is notable for its biodiversity and high proportion of endemic plants adapted to its semi-arid environment. Among its prominent tree species, Myracrodruon urundeuva (Aroeira) stands out due to its extensive distribution and economic value. Despite its significance, little is known about the environmental factors influencing its distribution. This study uses species distribution modeling (SDM) to assess the current and potential distribution of M. urundeuva and its habitat suitability under various climate change scenarios. Utilizing models like GLM, GAM, and BRT, and MaxEnt, the research analyzes georeferenced occurrence data and bioclimatic variables (selected by the variance inflation factor) from precipitation and temperature metrics. Our findings indicate that M. urundeuva is projected to experience relative stability or slight expansion in suitable habitats under future climate scenarios, including the pessimistic SSP585 scenario. However, localized habitat losses may occur, particularly in certain regions and timeframes, highlighting the complex and regionally variable impacts of climate change. This study emphasizes the need for localized and regional action plans to mitigate climate change impacts on M. urundeuva’s habitats. Conservation efforts should target areas identified as stable, ensuring the species’ resilience against escalating climate threats, thereby preserving one of its critical habitats within the Caatinga.